Assessing Determinants of Farmer’s Participation in Sugarcane Contract Farming in Indonesia - Rokhani, Rokhani; Rondhi, Mohammad; Kuntadi, Ebban Bagus; Aji, Joni Murti Mulyo; Suwandari, Anik; Supriono, Agus; Hapsari, Triana Dewi (Universitas Muhammadiyah Yogyakarta, 2020)
The integrated value chain is a prerequisite for the successful industrialization of the agricultural sector. Contract farming (CF) is a useful instrument to integrate the agricultural value chain in developing countries such as Indonesia. The purpose of this study was to identify the determinants of farmer participation in sugarcane contract farming. The data utilized in this study was obtained from the Indonesian Plantation Farm Household Survey 2014 for Sugarcane. The data consists of 8.831 farmers distributed in 8 provinces. Logistic regression was used to estimate the determinants of farmer participation in sugarcane CF. The result shows that age, education, and type of cultivated land negatively affect farmer participation in sugarcane CF. Meanwhile, land tenure, cultivation area, cropping system, certified seed, membership in a cooperative, access to extension services, and membership in farmer’s association positively affect farmer participation in sugarcane CF. The policy implication for increasing farmer participation in CF is to intensify the information of CF to the farmer with a large cultivation area. Since these farmers tend to participate in CF to anticipate marketing risks.